Case Report: A Novel Single Variant TJP2 Mutation in a Case of Benign Recurrent Intrahepatic Cholestasis. Issue 3 (25th August 2021) - Kornitzer, Gaël A.; Alvarez, Fernando
Abstract : Benign recurrent intrahepatic cholestasis (BRIC) is a disease on the spectrum of familial intrahepatic cholestasis caused by homozygous ABCB11 or ATP8B1 mutations. In recent years, genetic testing has allowed for discovery of a variety of homozygous or compound heterozygous TJP2 mutations associated with progressive familial intrahepatic cholestasis and intrahepatic cholestasis of pregnancy. To our knowledge, no cases of BRIC caused by a single variant mutation of TJP2 have been reported. We describe a 15-year-old female presenting with recurrent episodes of jaundice, vomiting, with intense pruritus, anorexia, and weight loss. Blood work revealed elevated serum conjugated bilirubin and liver enzymes but normal gamma-glutamyl transferase, consistent with BRIC. A genetic panel identified a not previously described single allele mutation in TJP2 of unknown functional significance. This is the first reported case of a clinical entity resembling BRIC with a heterozygous mutation in TJP2, without associated mutations in other cholestasis-related genes.